Giving Intention Versus Giving Behavior: How Differently Do Satisfaction, Trust, and Commitment Relate to Them?. (October 2019) - Shang, Jen; Sargeant, Adrian; Carpenter, Kathryn
This research quantifies for the first time in the literature how strong the direct and indirect relationships are between satisfaction, trust, and commitment and giving intention versus giving behavior. We constructed a unique data set of over 17, 000 donors from five large charities. We applied the latest mediation framework for categorical variables from consumer behavior. We found that at a group level, most of the direct and indirect effects that exist between satisfaction, trust, commitment, and giving intention also exist between these factors and giving behavior, but the effect sizes are between 3 to 8 times larger in modeling giving intentions than in modeling giving behavior. When giving intention and giving behavior are matched at an individual level, all group-level findings are replicated. In addition, we found 27% of the donors with no intention to give, actually gave. Theoretical, empirical, methodological, and practical implications are discussed.